The Influence of Recruitment Policy, Psychological Support, and Job Satisfaction on Civil Servant Retention at the Attorney General's Office - Ratri Ismawati; Dudung Hadiwijaya; Imam Muttaqijijin (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research aims to analyze and determine the influence of recruitment policy, psychological support factors, and job satisfaction on the retention of civil servants (ASN) at the Attorney General's Office. The research employs an explanatory research design with a quantitative approach, and the population includes all ASN employees at the Attorney General's Office, with a sample size of 100 employees. Data collection utilizes a survey method, and questionnaires are distributed to ASN employees at the Attorney General's Office. Multivariate statistical methods are employed for data analysis, revealing that transparent and competence-oriented recruitment policies have a positive impact on ASN retention. Additionally, psychological support provided by superiors and colleagues proves to significantly enhance ASN retention. On the other hand, job satisfaction among ASN employees plays a crucial role in influencing decisions to remain in the institution. This research provides a deeper understanding of the factors affecting ASN retention at the Attorney General's Office. The findings contribute to the development of more effective human resources policies and assist the institution in retaining and enhancing the potential of qualified ASN. These results are expected to serve as a reference for the Attorney General's Office and other researchers interested in the field of human resource management in the government sector.